Persons liable for the content of the prospectus - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Prospectus is a technical-legal instrument used in the capital market for informing potential investors. Liability for the content of the prospectus can be a result of the content’s deficiency. Content of the prospectus is deficient if it is not in accordance with legal rules regulating its completeness, truthfulness and transparency. As for a particular type of deficiency, the prospectus can be incorrect, incomplete or deceptive. The issue of liability for the prospectus’ content is very complex. The subject matter of this paper is restricted to defining persons liable and conditions of their liability for the content of the prospectus. The Law on the Capital Market (hereinafter: the LCM) regulates potential liability of the wide number of persons. However, it does not, in most instances, define conditions under which those persons are liable for the content of the prospectus. The paper discusses the liability of each person which is, by virtue of the LCM, potentially liable for the content of the prospectus and also contains a short glimpse on solutions from comparative law. Furthermore, the author underlines a need for a change of the provision which a priori excludes liability of the regulatory body  – the Securities Commission
Keywords: securities; issuer; liability for the content of the prospectus; prospectus